Unconventional Monetary Policies : Recent Experiences and Prospects. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This paper provides background information to the main Board paper, 'The Role and Limits of Unconventional Monetary Policy.' This paper is divided in five distinct sections, each focused on a different topic covered in the main paper, though most relate to bond purchase programs. As a result, this paper centers on the experience of the United States Federal Reserve (Fed), the Bank of England (BOE) and the Bank of Japan (BOJ), mostly leaving the European Central Bank (ECB) aside given its focus on restoring the functioning of financial markets and intermediation. Section A explores whether bond purchase programs were effective at decreasing bond yields and, if so, through which channels. Section B goes one step further in evaluating whether bond purchase programs had-or can be expected to have-significant effects on real growth and inflation. Section C studies the spillover effects of bond purchases on both advanced and emerging market economies, using very similar methods as introduced in the first section. Section D breaks from the immediate focus on bond purchases to discuss how inflation might decrease the debt burden in advanced economies, in light of possible pressures that could fall (or be perceived to fall) on central banks. Finally, Section E discusses the possible risks of exiting given the very large central bank balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet